A brief review of skull base chordomas - Syeda Kubra Kishwar Jafri; Ahsan Ali Khan; Duarte Nuno Crispim Candido; Muhammad Shahzad Shamim (Journal of the Pakistan Medical Association, 2023)
Skull base chrodomas are slow growing neoplasms usually located along the midline. They display a locally invasive nature with possibilities of extracranial metastasis. Presentation is usually late and depends upon the location and extent of the tumour. Management aims at gross total resection via open microsurgical or endoscopic approach followed by adjuvant radiotherapy. Prognosis may be good for the classical and chondroid subtypes but remains poor for de-differentiated type. Keywords: Chordoma, skull base, surgical management, radiotherapy.